Cecal volvulus, an uncommon cause of lower intestinal obstruction: case report and literature review - Rogelio Agustin, Blaz-Zavala; Karen Julissa, Pinto-Juarez; Milton, Valencia-González; Astrid, Ortiz-Vargas; Yanetzy Elizabet, Corona-Flores (International Journal of Research in Medical Sciences, 2023)
A volvulus is defined as a loop of bowel that undergoes torsion and rotation about its axis and the supporting mesentery, resulting in manifestations of intestinal occlusion. Depending on the degree of intestinal distension, blood flow may be compromised with risk of ischemia and perforation. Cecal volvulus is caused by axial rotation of the cecum, involving the terminal ileum and ascending colon due to alterations in fixation of the cecum. We present a case report of a 32-year-old male patient with no important surgical history who presented with lower intestinal occlusion secondary to cecum volvulus associated with flanges.